The strategies of NLRP3 inflammasome to combat Toxoplasma gondii - Yoon, Chanjin; Ham, Yu Seong; Gil, Woo Jin; Yang, Chul-Su (Frontiers in Immunology, 2022)
Infection with the protozoan parasite Toxoplasma gondii (T. gondii) results in the activation of nucleotide-binding domain leucine-rich repeat containing receptors (NLRs), which in turn leads to inflammasome assembly and the subsequent activation of caspase-1, secretion of proinflammatory cytokines, and pyroptotic cell death. Several recent studies have addressed the role of the NLRP3 inflammasome in T. gondii infection without reaching a consensus on its roles. Moreover, the mechanisms of NLRP3 inflammasome activation in different cell types remain unknown. Here we review current research on the activation and specific role of the NLRP3 inflammasome in T. gondii infection.